Wideband DS-CDMA for next-generation mobile communications systems. - Adachi, F. (IEEE Communications magazine)
Wideband wireless access based on direct sequence code division multiple access aimed at third-generation mobile communications systems is reviewed. W-CDMA is designed to flexibly offer wideband services which cannot be provided by present cellular systems, with various data rates as high as 2 Mb/s. The important concept of W-CDMA is the introduction of intercell asynchronous operation and the pilot channel associated with individual data channels. Intercell asynchronous operation facilitates continuous system deployment from outdoors to indoors. Other technical features of W-CDMA include fast cell search under intercell asynchronous operation, fast transmit power control, coherent spreading code tracking, a coherent RAKE receiver, orthogonal multispreading factor forward link, and variable-rate transmission with blind rate detection. The introduction of the data-channel-associated pilot channel allows W-CDMA to support interference cancellation and adaptive antenna array techniques that can significantly increase the link capacity and coverage. This article presents the radio link performance evaluated by computer simulation. Field experiment radio link performance results are also presented